The Describer's dictionary : a treasury of terms and literary quotations - Grambs, David; Levine, Ellen S. (New York : W.W. Norton & Company, 2015)
A singular and indispensable reference tool, The Describer's Dictionary now expanded and updated has served for over twenty years as the go-to resource for writers who are determined to capture the world in just the right words. The dictionary uses a unique reverse definition-to-term format that makes it easy to zero in on the term you're seeking. Turn to the new section on sensory impressions, for example, to find vivid terms for "loud or jarring," such as "grating," "harsh," "piercing," "blaring," "thunderous," "cacophonous," and "raucous." And at the end of each section dozens of illustrative passages by notable fiction and nonfiction authors including Donna Tartt, Michael Lewis, Zadie Smith, Khaled Hosseini, and Paul Theroux bring the terminology to life. New in this edition: Hundreds of additional definitions, terms, and synonyms Brand-new categories, including "Physical States and Symptoms," "Temperament and Behavior," "Rooms and Interior Spaces," "Weather and Forces of Nature," and "The Solar System." Over 400 new quotations from books, periodicals, and digital media by established and rising literary stars including an index of the more than 600 authors quoted in the book."
Previous edition: 1993.
Includes bibliographical references and index.
Keywords: English language -- Synonyms and antonyms; Description (Rhetoric); Description (Rhetoric); English language -- Synonyms and antonyms; Englisch; Synonymie